Undernutrition in inactive and mildly active Crohn's Disease : an unrecognised problem? - Nic Suibhne, Treasa (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2009)
Crohn's disease (CD), the incidence of which is increasing worldwide, is a chronic transmural inflammatory disease that can affect any part of the gastrointestinal tract. It follows a relapsing remitting course and results in symptoms such as weight loss, diarrhoea and abdominal pain. Undernutrition is a common feature of active disease, with weight loss and malnutrition apparent during flare-ups and periods of high disease activity affecting up to 85% of patients. On the other hand, during disease remission or at times of low disease activity, undernutrition is not so apparent and can be difficult to diagnose as most patients in remission look and feel well and lack the typical signs normally associated with malnutrition. However, as subclinical inflammation and symptoms predisposing patients to undernutrition can persist, and treatments such as corticosteroids can add to the risk of undernutrition (as they cause muscle wasting and bone loss but can also lead to weight gain and redistribution of body fat); undernutrition can occur and remain un-noticed due to weight gain.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin